2013
DOI: 10.1007/s00436-013-3429-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Theileria equi, Babesia caballi, and Anaplasma phagocytophilum in horses from the north of Portugal

Abstract: Piroplasmid protozoa Theileria equi and Babesia caballi and zoonotic rickettsial bacterium Anaplasma phagocytophilum are important agents of equine vector-borne diseases (EVBD). This study aimed at investigating the prevalence of infections with or exposure to these pathogens in horses from the north of Portugal. Blood was randomly collected from 162 horses, living in 72 different stables, to prepare Giemsa-stained slide smears. Additionally, plasma samples were tested for antibodies to T. equi and B. caballi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
4
16
1
1
Order By: Relevance
“…Previous studies conducted in Portugal report the detection of this pathogen in samples collected from horses (Baptista et al, 2013;Ribeiro et al, 2013) but, to date, no reports were found relating R. bursa with T. equi in our country. Equine piroplasmosis is endemic in the north of Portugal (Ribeiro et al, 2013) and it is estimated that 90% of the equine population worldwide lives in areas where equine piroplasmosis is present (Dewaal, 1992). Nowadays, equine piroplasmosis has serious implications for increasing international trade of horses (Ros-Garcia et al, 2013).…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies conducted in Portugal report the detection of this pathogen in samples collected from horses (Baptista et al, 2013;Ribeiro et al, 2013) but, to date, no reports were found relating R. bursa with T. equi in our country. Equine piroplasmosis is endemic in the north of Portugal (Ribeiro et al, 2013) and it is estimated that 90% of the equine population worldwide lives in areas where equine piroplasmosis is present (Dewaal, 1992). Nowadays, equine piroplasmosis has serious implications for increasing international trade of horses (Ros-Garcia et al, 2013).…”
Section: Discussioncontrasting
confidence: 60%
“…Numerous studies conducted outside Korea have also reported seropositivity for A. phagocytophilum in horses: 73% (67/90) of horses in the Czech Republic tested positive by IFAT (Praskova et al 2011); 13% (21/162) of horses in Portugal tested positive by IFAT (Ribeiro et al 2013); 13.7% (41/300) and 6.7% (20/300) of horses in Italy tested positive by IFAT and PCR, respectively (Laus et al 2013);16.3% (56/343) of horses in Tunisia tested positive by IFAT (Ben Said et al 2014); and 10.1% (45/444) and 9.0% (40/444) of horses in Italy tested positive by IFAT and ELISA, respectively (Veronesi et al 2014). The prevalence of seropositivity in the present study was lower than that reported in these studies; however, it is consistent with another Korean study that showed 2.2% (2/92) seropositivity for A. phagocytophilum in horses reared on Jeju Island, as determined by IFAT (Chae et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The EP prevalence was higher than in Spain in countries such as Colombia (≥90%) [98], Brazil 78.8% and 65.7% for T. equi and B. caballi , respectively, [44] or 97.5% for EP [100] and Mongolia with 82.3% EP seroprevalence [16], or 78.8% for T. equi and 65.7% for B. caballi , respectively [84]. However, it was lower in countries such as the UAE (33.3%) [48], Sudan (25.2%) [85], Portugal (17.9% and 11.1% for T. equi and B. caballi , respectively) [80], Turkey (18.4–18.5%) [51, 90], Jordan (14.6%) [2], Greece (11.6%) [56], Saudi Arabia (10.4% and 7.5% for T. equi and B. caballi , respectively) [6], Italy (8.5%) [40], Switzerland (7.3%) [92], the Netherlands (4%) [19] and Korea (1.1%) [87]. In other studies, the T. equi seroprevalence was higher than that described in Spain, but the seropositivity for B. caballi was lower, this is the case for France (from 58% to 80% for T. equi and from 1.2% to 12.9% for B. caballi ) [33, 38] and Iran (48% and 2%) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other authors showed the absence of an age-prevalence relationship [1, 3, 8, 10, 17, 23, 26, 36, 40, 46, 69, 75, 76, 80, 92, 94]. The present study pointed out that less than 1/4 of the foals and yearlings were seropositive for both parasites, with an increase in the percentage of infected horses until stabilisation at 11 and 14 years of age for T. equi and B. caballi, respectively, as Cantú-Martínez et al reported [23].…”
Section: Discussionmentioning
confidence: 99%